Diversity of phytophagous mites and their natural enemies of fruit crops in Kerala - Madhusudhan, M; Neena Lenin (Guide) (Vellayani Department of Entomology, College of Agriculture, 2025)
The study entitled (3z(BDiversity of Phytophagous Mites and their Natural Enemies of Fruit Crops in Kerala(3y (Bwas undertaken in the Department of Entomology, College of Agriculture, Vellayani, during 2022-2024. The major objective of the study was the documentation of the incidence, diversity and natural enemies of phytophagous mites inhabiting fruit crops in Kerala. Purposive sampling was conducted across 14 districts of Kerala, covering orchards, homesteads and other agricultural farms. The mite harbouring leaf samples were collected, labelled separately and transported in airtight polythene bags to the laboratory for further studies. The samples were observed under a stereo-binocular zoom microscope and permanent slides were prepared using Hoyer$1 (Bs media. Observations of these slides under a phase contrast microscope with image analyser revealed 50 species of mites under 34 genera and 16 families on 27 fruit crops. Out of these 50 mite species, 27 species were phytophagous and 23 were predatory. Out of the 27 fruit crops showing mite presence, banana recorded maximum number of mites (18) including 10 phytophagous and 8 predatory mite species. Phytophagous mite family Tetranychidae was represented by maximum number of species/genera (15/5), followed by Eriophyidae (4/4), Tenuipalpidae (3/2), Tarsonemidae (2/2), Diptilomiopidae (1/1), Acaridae (1/1) and Tydeidae (1/1). The broad mite, Polyphagotarsonemus latus (Banks) was collected from maximum number (16) of fruit crops. Genus Tetranychus Dufour showed the highest diversity with seven species. Banana recorded highest number of phytophagous mites with 10 species. Among predatory mites collected, family Phytoseiidae recorded maximum number of species/genera (10/6) followed by Tydeidae (3/3), Cheyletidae (2/2), Cunaxidae (2/2), Stigmaeidae (2/1), Eupodidae (1/1), Bdellidae (1/1), Erythraeidae (1/1) and Ameroseiidae (1/1). Genus Amblyseius Berlese showed the highest diversity with a record of five species. Maximum number of predatory mite species was recorded on Guava (10). In addition to predatory mites, other natural enemies of phytophagous mites belonging to the Class Insecta were also recorded, representing six families, namely, Coccinellidae, Staphylinidae, Ceciidomyidae, Thripidae, Hemerobiidae and Syrphidae. The study recorded new host plants for phytophagous mites including jackfruit as the new host for Tetranychus macfarlanei Baker and Pritchard, Tetranychus fijiensis Hirst and Eutetranychus orientalis Klein; passion fruit as the new host for Tetranychus truncatus Ehara; banana for Tetranychus udaipurensis Gupta & Gupta and T. macfarlanei; papaya as the new host for T. udaipurensis; sitaphal, peanut butterfruit and hog plum for Brevipalpus phoenicis (Geijskes); peanut butterfruit, hog plum, pomegranate, santol and abiu as the new hosts for Brevipalpus californicus (Banks). Eriophyid mite, Tegolopus indica Chakrabarti & Mondal, and phytoseiid mite Amblyseius tamatavensis Blommers are the new reports from the state. The study highlights the diversity and incidence of phytophagous mites as well as their natural enemies on 27 fruit crops in Kerala. It also sheds light on the host range and specificity of phytophagous mites on fruit crops. The details of new host plants recorded adds to the present knowledge, while, the information on predatory mites and other insect predators can be further explored for building innovative biological control programs against pest mites that have a potential to become possible threat in the future to fruit ecosystem.s
MSc
Keywords: Entomology; Phytophagous mites; Fruit crops; Kerala